Interpretation of the Symbolic Meaning in the Sri Kayun Traditional Dance in Kulon Progo Regency - Fadila Ramadante; Siany Indria Liestyasari (Mahesa Research Center (PT. Mahesa Global Publishing), 2026)
This study examines the Sri Kayun dance, which has served as the official welcoming dance of Kulon Progo Regency since 2022. This research aims to identify, describe, and interpret the symbolic meanings embedded in the movements of the Sri Kayun dance, as well as the cultural values that underlie it. The study is guided by a semiotic approach to explain how symbolic meanings are constructed and represented within the performance. The research employs a descriptive qualitative method using a case study approach. Data were collected through observation, interviews, literature reviews, and documentation. The findings reveal that the name